2000
DOI: 10.1097/00001813-200001000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of dextran derivatives immobilizing platinum complex (II)

Abstract: The in vivo antitumor activity and toxicity of a newly synthesized polymeric prodrug of cisplatin was investigated and also compared with plain cisplatin. The prodrug included a dicarboxymethyl-dextran conjugate of cisplatin (DCM-Dex/CDDP). DCM-Dex/CDDP was i.v. injected in mice bearing s.c. Colon 26 mouse colon cancer cells. The tissue distribution of platinum was thereafter determined by flameless atomic absorption spectrophotometry. The platinic concentration of the organs showed a high rate of retention at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Due to its biocompatibility and immunoneutrality, dextran is extensively employed as a bioinert material in biomedical science, tissue engineering, and drug delivery systems. [1][2][3][4][5] In addition, dextran has confluent moieties for chemical conjugation, ie, a hydroxyl group exists in each glucose unit. Therefore, dextran is frequently investigated for use as a drug carrier system for anticancer drugs, antidiabetic agents, antibiotics, peptides, and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its biocompatibility and immunoneutrality, dextran is extensively employed as a bioinert material in biomedical science, tissue engineering, and drug delivery systems. [1][2][3][4][5] In addition, dextran has confluent moieties for chemical conjugation, ie, a hydroxyl group exists in each glucose unit. Therefore, dextran is frequently investigated for use as a drug carrier system for anticancer drugs, antidiabetic agents, antibiotics, peptides, and enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Because dextran is biocompatible, biodegradable, and immunoneutral, it is extensively employed for modification of bioactive materials. 21,[25][26][27][28] Further, dextran has the potential to avoid unwanted protein or cellular absorption and to increase the blood circulation time, depending on molecular weight. [29][30][31] Dextran has also been used to deliver anticancer agents in systemic drug delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the cytotoxicity of the MTXester-dextran and MTX-amide-dextran were equivalent to unmodified MTX however the conjugation resulted in shifting of dose-response curve to a lower dose (156). Also, Ichinose et alsynthesized dicarboxymethyl dextran conjugate of cisplatin by immobilizing cisplatin to dextran polymer chain through six-membered chelating coordinate bond which exhibited remarkably longer half-life and better tumour inhibition activity than pure cisplatin in the colon (157). Charged dextran derivatives such as carboxymethyl dextran, dextran sulphate and diethylaminoethyl dextran can also form complexes with several small bioactive chemical entities due their huge numbers of hydroxyl groups available for complexation and can be extensively explored as drug carrier systems because they are biocompatible, biodegradable, non toxic, non immunogenic and non antigenic.…”
Section: Natural Polysaccharidesmentioning
confidence: 99%